Mauritania : Joint Staff Advisory Note of the Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2011)
Mauritania's third poverty reduction strategy paper provides a framework for an ambitious growth and poverty reduction agenda. The updated development perspective and principal objectives reflect the new economic and political realities to sustainably reduce poverty. Successful program implementation hinges on the government's ownership and commitment. It will only succeed if the institutional framework remains stable, and the civil society is engaged on a permanent basis. Ensuring a broad social consensus for the strategy will make it easier to mobilize donor resources, thus easing financing constraints.